ANALYSIS OF PUMPING TEST AND GROUNDWATER QUALITY IN MANGGIS DISTRICT, KARANGASEM REGENCY, BALI PROVINCE - Ridho, Muhammad
The research area is administratively located in Manggis District, Karangasem Regency, Bali Province which covers an area of 9.74 km2